Place-pedagogies of water stress - Anna Wilson; Gillian Black; Leif Petersen; Liezl Dick; Sikhululekile Ncube; Tsitsi Mpofu-Mketwa; Amber Abrams; Kirsty Carden; Laurence Piper; Jen Dickie; Niall Hamilton-Smith; Guy Lamb (Global Social Challenges Journal)
This article explores the pedagogical affect of water in a place of water stress and illustrates its entanglement with dynamics of power and control. The current climate crisis is rendering already drought-prone regions ever drier, and it is often the already socially and economically disadvantaged who experience the most immediate impacts. In this article, we describe the experiences of residents in one township in South Africa’s Cape Flats to explore how water literacies have developed and been reinforced by a prolonged period of water scarcity. By analysing assemblages of images and accompanying texts produced through a PhotoVoice process undertaken by co-researchers in this settlement, we show how water’s presence as an always imminent absence has profound pedagogical impact. We also explore how water manages to escape and flow outside of attempts to control and constrain it. Finally, we speculate on the implications for place-based water literacies and the pedagogies at work in other places of water stress.